An enzyme-assisted electrochemiluminescent biosensor developed on order mesoporous carbons substrate for ultrasensitive glyphosate sensing. (20th December 2015) - Zhang, Qingrong; Xu, Guifang; Gong, Lingshan; Dai, Hong; Zhang, Shupei; Li, Yilin; Lin, Yanyu
Abstract: In this paper, a strategy of developing a late-model and sensitive electrochemiluminescence (ECL) biosensor for glyphosate detection based on enzyme-assisted in situ generation of ZnS quantum dots (QDs) on ordered mesoporous carbons (OMC) substrate was proposed. OMC, as a typically ordered mesoporous carbon material, not only provides a protective microenvironment for enzyme to retain its structure and activity but also has a synergistic effect with chitosan for the absorption of Zn 2+ ions by virtue of its high surface area and high pore volume and thus employed as the matrix of proposed biosensor. Then horseradish peroxidase (HRP) was introduced to expedite the generation of ZnS QDs via accelerating the reduction of Na2 S2 O3 with H2 O2 to yield H2 S that reacted with Zn 2+ ions. Glyphosate, as a kind of organic pesticide with amine, carboxyl and phosphonate group which would coordinate strongly to metal ions, possessed the potential to inhibited the activity of HRP, because HRP contain iron (III) protoporphyrin IX (ferriprotoporphyrin IX) as the prosthetic group which would react with the amine, carboxyl and phosphonate group of glyphosate. Accordingly, the proposed ECL QDs biosensor was employed to determine the Gly and shown a wide linear range from 0.1 nM to 10 mM with excellent sensitivity, reproducibility and selectivity. Further, the half maximal inhibitory concentration (IC50 ) and the Michaelis–Menten constant were studied, and all the results indicated that the proposed strategy is practicable and provide a new opportunity to develop novel ECL sensing platforms in various applications.